Leadless pacemaker implant with concomitant atrioventricular node ablation: Experience with the Micra transcatheter pacemaker. (23rd January 2021) - El‐Chami, Mikhael F.; Shinn, Timothy; Bansal, Sundeep; Martinez‐Sande, Jose L.; Clementy, Nicolas; Augostini, Ralph; Ravindran, Bipin; Sagi, Venkata; Ramanna, Hemanth; Garweg, Christophe; Roberts, Paul R.; Soejima, Kyoko; et al.
Abstract: Background: The feasibility and outcomes of concomitant atrioventricular node ablation (AVNA) and leadless pacemaker implant are not well studied. We report outcomes in patients undergoing Micra implant with concomitant AVNA. Methods: Patients undergoing AVNA at the time of Micra implant from the Micra Transcatheter Pacing (IDE) Study, Continued Access (CA) study, and Post‐Approval Registry (PAR) were included in the analysis and compared to Micra patients without AVNA. Baseline characteristics, acute and follow‐up outcomes, and electrical performance were compared between patients with and without AVNA during the follow‐up period. Results: A total of 192 patients (mean age 77.4 ± 8.9 years, 72% female) underwent AVNA at the time of Micra implant and were followed for 20.4 ± 15.6 months. AVNA patients were older, more frequently female, and tended to have more co‐morbid conditions compared with non‐AVNA patients ( N = 2616). Implant was successful in 191 of 192 patients (99.5%). The mean pacing threshold at implant was 0.58 ± 0.35 V and remained stable during follow‐up. Major complications within 30 days occurred more frequently in AVNA patients than non‐AVNA patients (7.3% vs. 2.0%, p < .001). The risk of major complications through 36‐months was higher in AVNA patients (hazard ratio: 3.81, 95% confidence interval: 2.33–6.23, p < .001). Intermittent loss of capture occurred in three AVNA patients (1.6%), all were within 30 days of implant and required system revision. There were no device macrodislodgements or unexpected device malfunctions. Conclusion: Concomitant AVN ablation and leadless pacemaker implant is feasible. Pacing thresholds are stable over time. However, patient comorbidities and the risk of major complications are higher in patients undergoing AVNA.